BARBOSA, Andréa. São Paulo, Cidade Azul. São Paulo: Alameda Casa Editorial, 2012. 256 p. - Pessuto, Kelen (ILUMINURAS, 2013)
BARBOSA, Andréa. São Paulo, Cidade Azul. São Paulo: Alameda Casa Editorial, 2012. 256 p.